La comunicación interna en el desarrollo organizacional de la Unidad Educativa Particular Santa Luisa de Marillac del cantón Mejía - Cevallos Caiza, Adriana Lisbeth (2023)
The Santa Luisa de Marillac Private Educational Unit is a private institution in Machachi, Pichincha province. It has 43 employees in different areas of the organization. The project with the theme "Internal communication in the organizational development of the Santa Luisa de Marillac Private Educational Unit" focused on internal communication in the organizational development of the institution. The objective of the research was to analyze the internal communication for the Organizational Development of the Santa Luisa de Marillac Private Educational Unit during the first quarter. In this research was used quantitative and inductive method, the direct observation technique was used as an instrument, the questionnaire, interview, and observation sheet were used, it is concluded that the institution does not have innovative technological tools to promote interaction and adequate communication among its members, the implementation of an internal communication plan is proposed as a proposal, where an ERP (Enterprise Resource Planning; Business) that allows the integration of all collaborators, achieving a more formal communication and an efficient organizational development that contributes to the fulfillment of institutional goals and objectives